Rancang Bangun Aplikasi Media Pembelajaran Interaktif Pengenalan Komputer Dan Kuis Pilihan Ganda Berbasis Web - Nunu Nugraha; Intan Permatasari (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2022)
This study aims to design and build the application of flash-based learning media on ICT subjects with the topic of computer introduction. This application was created as a learning medium for students of class XI MTs Al Ma'Mur Ciawigajah. Flash-based learning media applications can be used as an alternative learning media for students. The method used in designing and building applications using the waterfall method consists of five stages, namely Requirement Analysis, System Design, Implementation, Integration, Testing, and Operation Maintenance. Based on the results of implementation and application testing, the application can run well in accordance with the required specifications and can be used as a medium for student learning. The quiz feature found in the learning application can be used as an evaluation material for teachers in providing an assessment of student learning outcomes.Keywords: Media, Learning, Flash, Computer, Application